Where Are My Houses? (Cinéma & Cie. Film and Media Studies Journal, 2017)
In recent years, several audiovisual works made in Italy by (partly or wholly) people hailing from the former Italian colonies of Eritrea, Ethiopia and Somalia have contributed to a challenge to the notions of displacement, deterritorialization and belonging in contemporary Italian society. They trouble the spaces of contact between people, of experiences and memories, therefore highlighting ‘the historical continuum and cultural genealogy’ (Lombardi-Diop and Romeo, 2012) between the colonial past and the present. By examining displacement and deterritorialization as possible expressions of belonging, rather than polarized elds in relation to it, this essay explores several examples where characters and lmic narrations assume the presence in the ‘here’, and the possibility to convert the ‘here’ into ‘home’, by modifying relations with people and places.